(E)‐1‐[(5‐Chloro‐3‐methyl‐1‐phenyl‐1H‐pyrazol‐4‐yl)methylidene]‐2‐phenylhydrazine: sheets built from π‐stacked hydrogen‐bonded chains. Issue 2 (16th January 2014) - Trilleras, Jorge; Utria, Michael; Cobo, Justo; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> The reaction between 5‐chloro‐3‐methyl‐1‐phenyl‐1H‐pyrazole‐4‐carbaldehyde and phenylhydrazine proceeds via condensation to provide the title compound, C17H15ClN4, (I), rather than via the alternative routes of simple nucleophilic substitution or cyclocondensation. With the exception of the phenyl group bonded directly to the pyrazole ring, the non‐H atoms of (I) are nearly coplanar, with an r.m.s. deviation of 0.058 Å. The molecules are linked into C(7) chains by a single N—H...N hydrogen bond, and the chains are linked by π–π stacking interactions to form sheets.